Implementation of the Policy on the Enforcement of Regional Regulations and Regional Head Regulations by the Civil Service Police Unit of Bali Province - I Putu Gede Agus Wiranata; Ida Ayu Putu Sri Widnyani; Gede Wirata (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
Abstract The Civil Service Police Unit (Satpol PP) of Bali Province faces several challenges in enforcing Regional Regulations (Perda) and Regional Head Regulations (Perkada). The main obstacles include limited human resources, the public’s lack of understanding of the regulations, overlapping authority with customary institutions, and a public perception of Satpol PP as repressive. This situation, combined with inconsistent law enforcement, leads to low public compliance. This study aims to thoroughly examine how Satpol PP can optimize its enforcement of these regulations. The main research problems are to identify the challenges and obstacles faced by Satpol PP and to formulate effective strategies for improving law enforcement in Bali. The research uses a qualitative approach, with data gathered from observations, interviews, and documentation. The findings indicate that optimizing Satpol PP’s role is crucial for maintaining public order and social stability in Bali. This is achieved by harmonizing legal certainty with the socio-cultural sensitivity of the Balinese community. A key strategy identified is strong cross-agency coordination with the police, prosecutors, and customary villages. This collaboration makes the law enforcement process faster, more accurate, and socially acceptable. Keywords: Optimization, Perkada, Civil Service Police Unit (Satpol PP)